Advancing Theories of Ecosystem Development through Long-Term Ecological Research. (18th July 2018) - Kominoski, John S; Gaiser, Evelyn E; Baer, Sara G
Abstract: Decades of place-based, long-term ecological research have generated important insights into patterns and processes among ecosystems. Here, we extend a theoretical framework based on Odum's "strategy of ecosystem development"—which predicted distinct attributes of developing and mature ecosystems—in the context of more recent theoretical advancements that predict how long-term changes in the presses (long-term, gradual changes) and pulses (abrupt changes) of drivers that regulate ecosystem functions (press–pulse regimes) can influence their trajectories of development. Our modifications to ecosystem development theories (a) illustrate how press–pulse regimes can cause ecosystems to continue to develop or oscillate around a stable state (pulsed stability) or cause them to decline if the press–pulse regime changes faster than species and communities can adapt, (b) use examples from long-term ecological research of how attributes interact to affect development, and (c) suggest how revised and new theoretical frameworks can integrate long-term ecological research and observatory networks.